AR : Prix Ariane de Rothschild Bruxelles = Ariane de Rothschild Prijs Brussel = Ariane de Rothschild Prize Brussels 2008. - Abu ElDahab, Mai; Bayar, Devrim; Bezzan, Cécilia; Doove, Edith; Gielen, Denis; Martens, Hans; Oliveira, Filipa; Rollin, Pierre-Olivier; Schuster, Aaron; Van Damme, Bram; de Rothschild, Ariane; de Tscharner, David; et al. (Bruxelles : Banque Privée Edmond de Rothschild Europe Bruxelles, 2008)
Balleux, Stephan ; Beaudry, Charlotte ; Bernadet, Jean-Baptiste ; Boubolis, Sofia ; Garabedian, Mekhitar ; Leech, Adam ; Lizein, Annick ; Moerman, Jean-Luc ; Neirings, David ; Plateus, Benoit ; Samyn, Fabrice ; Timmermans, Ante ; Vranken, Leon ; Wambacq, Freek
HB : groot formaat zie speciale kast
biog., tent. p. 56-59
Engels
Frans
Nederlands
boek